Strengthening Financial Accountability in Faith-Based Public Services: Lessons from Mosque Governance in Indonesia - Anggraeni, Rasmi Nur; Amir, Andi Mattulada; Rajindra, Rajindra; Septiana, Nani; Praditha, Riza (Jurnal Aplikasi Manajemen, 2026)
Mosques are important in controlling the community finances. Nevertheless, they do not always go smoothly, and these problems include the absence of transparency in reporting, uneven or unstructured record-keeping, and disorganized financial reports. This may result in the erosion of the popular belief, should this be maintained, and this would have an impact on the stability of the mosque. The study being conducted will attempt to establish the relationship between the management of mosques and financial transparency and accountability. In addition, the case study was performed qualitatively in the Donggala Grand Mosque, Central Sulawesi, between March and June 2024. The respondents were seven people who described how they handle mosque finances on a day-to-day basis: two administrators of the mosque, one treasurer, and four active congregants. The semi-structured interviews, direct observation of mosque activities, and analysis of available financial reports were used in the collection of data. The results indicate that frequent review of financial reports accompanied by simple cash flow records can lead to an improved understanding of the people in the congregation about their financial data. This will also serve in establishing a donor confidence and make it easier to manage mosque fund accountability as per the needs of the community. Finally, this study demonstrates that Islamic principles of ethical behavior and proper financial management may result in the improved management of mosques and make them open and responsible. Besides this, this study further enhances the role played by stakeholders like the policymakers, the Islamic philanthropic institutions, and the administrators of mosques to know how they can improve their financial management in the future.